Perancangan Flowmeter Ultrasonik untuk Mengukur Debit Air Pada Pipa - Hidayahtullah Abdi Robhani; Abdul Ro'uf (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2018)
Measurement of water discharge using ultrasonic wave properties ensures the stability of measured water profile because of its non-intrusive nature. In this study, a water discharge measuring device has been developed by utilizing ultrasonic wave properties to determine its speed. The device is designed using two pairs of ultrasonic transmitters and receivers at upstream and downstream positions toward the direction of the water flow. 40 kHz ultrasonic waves are generated with AD9850 DDS sinusoidal pulse generating module. The sensor data processor uses an Arduino Due microcontroller module by calculating the measured ultrasonic wave travel time difference.             Measurements were made on a 57 mm diameter pipe with flow rates varied using 25%, 50%, 75%, and 100% tap openings. The measurement resulte shows the lowest water debit calculation value of 4.42×10-4 m3/s at 25% faucet opening and highest discharge of 2.15×10-3 m3/s at 100% faucet opening with the values of coefficient of correlation and coefficient of determination on 25%, 50%, 75% and 100% faucet openings respectively 0.9715, 0.9669, 0.9604 and 0.9647 and 94.37%, 93.49%, 92 , 24%, and 93.07%.